Islamic Store Brand Engagement and Customer Loyalty Relationship - Warsito, Chandra; Farhah, Nida Umi; Adawiyah, Wiwiek Rabiatul; Wahab, Norailis Ab. (IKONOMIKA, 2022)
This study aims to develop a new construct approach to consumer brand engagement that bridges the relationship between satisfaction, trust and commitment to customer loyalty. This study fills the void by examining the mediating role of Islamic store brand engagement to solve the inconsistency in the relationship between satisfaction, trust, and commitment to consumer loyalty. The study surveyed 375 shop customers with Islamic attributes in Central Java Indonesia region research samples. This study’s results can be applied as a new marketing strategy for stores with Islamic attributes by practicing Islamic values in business, highlighting the existence of halal products, creating and maintaining an Islamic atmosphere at the shop, and practicing Islamic-based humanistic services.